2022
DOI: 10.1038/s41420-022-01137-8
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin ameliorates acute lung injury by modulating NLRP3 inflammasome-induced pyroptosis

Abstract: We commenced to analyze putative anti-pyroptosis effects of puerarin (PU) as mediated by the PP2A-HDAC1-NLRP3 pathway in acute lung injury (ALI). ALI animal and cell models were constructed, followed by treatment of PU. Then, the effect of HDAC1, PP2A, and NLRP3 on cell inflammation and pyroptosis was explored. The interaction between HDAC1 and PP2A as well as between PP2A and NLRP3 was analyzed. Our findings suggested that PU downregulated HDAC1 expression to alleviate symptoms of ALI. HDAC1 overexpression pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Impaired energy metabolism, resulting in a depletion of cellular ATP, which is critical for normal brain function, is another consequence of mitochondrial damage [ 36 ]. Furthermore, mitochondrial dysfunction can contribute to the activation of apoptotic pathways, which worsen brain damage in SAE [ 41 ]. This damage may be a compensatory response to increased energy demands, and may contribute to cognitive and emotional dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired energy metabolism, resulting in a depletion of cellular ATP, which is critical for normal brain function, is another consequence of mitochondrial damage [ 36 ]. Furthermore, mitochondrial dysfunction can contribute to the activation of apoptotic pathways, which worsen brain damage in SAE [ 41 ]. This damage may be a compensatory response to increased energy demands, and may contribute to cognitive and emotional dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…A novel crystal type V (Puer-V) was found to have a better therapeutic effect than the crude form of puerarin, effectively alleviating abnormal structural changes and dysfunction in lung tissue and the right ventricle [ 78 ]. Puerarin also exhibited anti-inflammatory properties in rats with acute lung injury by modulating the renin–angiotensin system and NF-κB signaling pathway, modulating the nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing-3 (NLRP3) inflammasome-induced pyroptosis, and reducing TNF-α, interleukin-6 (IL-6), and interleukin-1β (IL-1β) production [ 79 , 80 , 81 ].…”
Section: Natural Products For the Treatment Of Phmentioning
confidence: 99%
“…In addition, clinical and preclinical evidence suggests that inflammasomes, particularly NLRP3 and its downstream cytokine products, are promising drug targets for PH [ 119 ]. Puerarin inhibits NLRP3 inflammasome-induced pyroptosis to improve acute lung injury [ 81 ]. Astragaloside IV has been shown to inhibit MCT-induced PH via the NLRP-3/calpain-1 pathway [ 90 ].…”
Section: Mechanism Of Natural Products For the Treatment Of Phmentioning
confidence: 99%
“… 24 , 25 , 26 Notably, previous studies reported that Pue exerted antioxidant and anti‐inflammatory effects, especially for the inhibition of ROS and NLRP3 inflammasome. 27 , 28 The specificity of Pue in addressing diabetes‐associated cardiovascular disease requires further clarification. This inquiry seeks to establish a coherent understanding of the mechanisms by which Pue exerts its effects on oxidative stress, inflammasome activation and pyroptotic cell death specifically within the context of diabetic vascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Notably, previous studies reported that Pue exerted antioxidant and anti-inflammatory effects, especially for the inhibition of ROS and NLRP3 inflammasome. 27,28 The specificity…”
Section: Introductionmentioning
confidence: 99%